Journalism and the Black Short Story in English in Twentieth-Century South Africa: From R. R. R. Dhlomo to Miriam Tlali - Fossati, Marta (Cadernos de Literatura Comparada, 2021)
In the present article I seek to discuss, following a diachronic approach, the close-knit relationship that can be found between journalistic discourse and the genre of the short story in Anglophone South African literature over a time span of fifty years, between the late Twenties and the Eighties. In particular, I intend to explore this genre negotiation by close reading selected short stories and/or newspaper articles by four non-white South African writers: R. R. R. Dhlomo, Can Themba, Alex La Guma, and Miriam Tlali. The intersections between the two different genres and discourses in these hybrid texts can be identified at the level of both content and form. A close reading of selected short stories and/or articles may call for a revaluation of this “South African New Journalism” as a creative experimentation that challenges conventional generic categorisations.